SOSIALISASI MASYARAKAT DESA TEGALREJO TERHADAP UU NOMOR 23 TAHUN 2004 TENTANG KEKERASAN DALAM RUMAH TANGGA DAN KESETARAAN GENDER - Koeshardjono, Hery; Sunarlin, Emmy; Candradewi W, Renny; Zakariyah, M. Abdi; Aszehra, Fatima; Lina, Shinta Mega; Yunus, Fiky; Hikam, Rifki Abdul (Abdi Panca Marga, 2023)
The problems in this activity are the lack of knowledge or information received by the community about domestic violence law; lack of legal understanding of the contents of Law Number 23 Year 2004 related to domestic violence; and the existence of domestic violence that is not found. Problem solving is done through legal communication. Legal communication is the process of delivering messages in accordance with the law that contains the contents of a legal rule, with the aim of creating mutual understanding or understanding of the law, resulting in changes in the thoughts, attitudes and behavior of the recipient, without any change. coercion from outside. This service activity is a seminar forum model with light dialog because it adjusts to the scope and quality of human resources at the service location. Delivery of material by dialog and giving examples in everyday life. The results of the activity show an increase in the understanding and knowledge of residents regarding the rules / laws governing the elimination of domestic violence, which initially had a knowledge value of 55.25, after implementing the project had a knowledge value of 74.75. Activities like this need to be carried out in the future, by continuing to provide understanding and knowledge related to community life rules. Keywords: Gender Equality, Domestic Violence, Household.